The Cumulative Effects of Marketized Care - Chatzidakis, Andreas; Eckhardt, Giana M; Husemann, Katharina C (Journal of Consumer Research, 2025)
Abstract Care is increasingly marketized. Previous marketing and consumer research has focused on specific tensions underlying marketized care provision and the ways in which consumers navigate them. In contrast, this conceptual article draws on interdisciplinary research on care to develop a cumulative understanding of marketized care, that is, based on those effects that build up over time when a critical mass of consumers routinely addresses care needs via markets. Defining marketized care as attending to the welfare needs of human and nonhuman others through the market, we identify four negative cumulative effects: individuating effects on consumer subjectivities, alienating effects on care relationships, responsibilizing effects on consumers as opposed to other institutional actors of care provision, and exploitative effects generated in global care and supply chains. We also outline four principles that can mitigate these effects: interdependent consumer autonomy, affective reconnections, proportionate responsibilization, and market reconfiguration. Our conceptualization moves the literature on marketized care forward by outlining its cumulative nature as well as offering potential solutions that are neither demonizing nor celebratory of markets. In doing so, we offer a series of generative insights for research on marketized care that contribute to addressing collective human and nonhuman flourishing.